(3GdQO hGdGfJUGQ dePgH SjO abgGA GdCeUGQ (B((3GdEeGe CHhMfjaI(B)s - (3eMeO Hf eMeO Hf YHO GdSJGQ, CHh GdhLO, TeS GdCFeI GdYeGOj GdcQOQj,J (B642 (3g` s
(3ChdgG (B:s
(3hHYO eG cfJ CSeY TaYhjoG jPe EeGe hSQGL GdCeI CHG MfjaI QVi Gdg Yfg s
(3BNQgG (B:s
(3agDdGA jUM GbJOGA cd efge HCi EeGe cGf ef ZjQ JaUjd aEfge dGePgH dge s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B28 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B233s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B381 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B654 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B193 s
(3eUOQ GbJfGA GdCUd (B:s
(3QhGb GdCJQGc (B- (3GdCRgQ (B((3JGQjN (B979) s
Keywords: (3GdJGQjNs